Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/0036933014548144
|View full text |Cite
|
Sign up to set email alerts
|

Polymyalgia rheumatica: 125 years of progress?

Abstract: Polymyalgia rheumatica remains a clinical enigma, and its relationship to giant cell arteritis is no clearer now than it has been for the past 125 years. Diagnosing this disease is still almost exclusively dependent on the clinical acumen of a patient's medical attendant. Until an objective method of identifying it clearly in the clinical setting is available, uncovering the aetiology is still unlikely, and until then, preventing the pain and stiffness of the disease while avoiding the problems of prolonged ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
(181 reference statements)
0
3
0
1
Order By: Relevance
“…There is considerable clinical and some immunogenetic overlap between GCA and PMR, with co-occurrence being almost 40 times more likely than would be expected if they were truly separate syndromes [14,15]. The precise nature of their relationship remains to be clarified and although there are distinct differences [16,17], the presence of PMR should alert clinicians to the possibility of GCA.…”
Section: Symptomsmentioning
confidence: 99%
“…There is considerable clinical and some immunogenetic overlap between GCA and PMR, with co-occurrence being almost 40 times more likely than would be expected if they were truly separate syndromes [14,15]. The precise nature of their relationship remains to be clarified and although there are distinct differences [16,17], the presence of PMR should alert clinicians to the possibility of GCA.…”
Section: Symptomsmentioning
confidence: 99%
“…Giant cell arteritis (GCA) incidence is highest in populations with Scandinavian ancestry [ 6 8 ] and this has led to suggestions that this might be due to genetic factors [ 9 , 10 ]. Susceptibility to GCA has been reported to be associated with carriage of HLA-DRB1 *04, but not all studies have shown an association and there are conflicting data as to whether there is an association with specific HLA-DRB1 *04 alleles [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymyalgia Rheumatica (PMR), a common inflammatory condition of elderly people [12], is characterized by pain in both shoulders and hips, elevated acute-phase reactants and a prompt response to corticosteroid therapy [13]. With these clinical features lacking specificity, it is often difficult to diagnose or classify subjects suspected of PMR [14].…”
Section: Polymyalgia Rheumaticamentioning
confidence: 99%